Detection of infant faecal bifidobacteria by enzymatic methods - Vlková, E; Nevoral, J; Jencikova, B; Kopecný, J; Godefrooij, J; Trojanová, I; Rada, V (Journal of microbiological methods, 2005)
An enzyme-based assay was developed for the detection of bifidobacteria in infant faeces. Ninety-five samples from 51 breast-fed infants in the age between 3 and 276 days were investigated. Bifidobacteria and other bacterial groups were determined by cultivation and fluorescence in situ hybridisation (FISH). Faecal samples were examined for the activity of fructoso-6-phosphate phosphoketolase (F6PPK) and for other enzymatic reactions using the API-ZYM kit. Twenty-nine infants had high numbers of bifidobacteria (usually higher than 9 log CFU/g) in their faeces. Seventeen infants (35%) did not contain detectable amounts of bifidobacteria in their faecal samples. The remaining five individuals had low counts of bifidobacteria (3-6 log CFU/g). Most negative infants possessed major amounts of clostridia in their faecal flora. There were no significant differences among bifidobacterial counts obtained by cultivation and FISH, detection of F6PPK, alpha-galactosidase and alpha-glucosidase activities could routinely be used for the rapid and simple detection of bifidobacteria in infant faecal samples. Bifidobacterial colonies were identified using enzymatic tests and PCR procedure based on 16S rRNA gene sequences species-specific primers. In 14 samples, the identifications of individual isolates were compared with direct analyses of faeces using the nested PCR-denaturing gradient gel electrophoresis (nested DGGE) procedure. The results obtained in several cases are not identical. Bifidobacterium longum and Bifidobacterium breve were most frequently identified. Bifidobacteria-positive samples had high activities of alpha-galactosidase and alpha-glucosidase. On the contrary, negative samples missed either one or both of these enzymatic activities. While all positive samples tested showed distinctive fructose-6-phosphate phosphoketolase activity (F6PPK), none of the negative samples expressed F6PPK activity.
Keywords: Feces; polymerázová řetězová reakce; Male; alpha-Galactosidase; hybridizace in situ fluorescenční; Glucuronidase; RNA, Ribosomal, 16S; Infant; aldehydlyasy; glykosidhydrolasy; mužské pohlaví; Aldehyde-Lyases; novorozenec; DNA, Bacterial; DNA bakterií; lidé; ženské pohlaví; Glycoside Hydrolases; glukuronidasa; Humans; Infant, Newborn; Bifidobacterium; kojenec; RNA ribozomální 16S; In Situ Hybridization, Fluorescence; Electrophoresis; Polymerase Chain Reaction; elektroforéza; alfa-galaktosidasa; Female; beta-Galactosidase; feces; beta-galaktosidasa